2020
DOI: 10.1140/epjp/s13360-020-00304-z
|View full text |Cite|
|
Sign up to set email alerts
|

Solutions of Schrodinger equation for the modified Mobius square plus Kratzer potential

Abstract: In this paper, we obtain the approximate solutions of the Schrodinger equation with the modified Mobius square plus Kratzer potential using the Nikiforov-Uvarov method and employing the approximation scheme for the centrifugal term. We obtain the energy eigenvalue equation and corresponding wave functions. Finally, some numerical results and special cases are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In the earlier study of quantum mechanics, the Schrödinger equation was introduced as a second-order differential equation capable of describing the properties of a non-relativistic Quantum system [1][2]. Studies have revealed that exact solutions of the Schrödinger equation are available only for a limited set of physical and chemical quantum mechanical systems [3][4]. Hence, with an approximation to the centrifugal term, interest is geared towards arbitrary -solutions of the radial Schrödinger equation.…”
Section: Introductionmentioning
confidence: 99%
“…In the earlier study of quantum mechanics, the Schrödinger equation was introduced as a second-order differential equation capable of describing the properties of a non-relativistic Quantum system [1][2]. Studies have revealed that exact solutions of the Schrödinger equation are available only for a limited set of physical and chemical quantum mechanical systems [3][4]. Hence, with an approximation to the centrifugal term, interest is geared towards arbitrary -solutions of the radial Schrödinger equation.…”
Section: Introductionmentioning
confidence: 99%
“…In quantum chemistry and molecular physics, Kratzer's potential is often considered to explain interactions in a molecular system. This potential is exactly solvable [12], and numerically solved by many methods, such as the asymptotic iteration method (AIM) [13][14][15][16][17][18][19][20][21][22]. This potential is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…dz . Several researchers applied PQR to physical potential problem [25][26][27][28][29][30][31][32][33][34][35] both in relativistic and non-relativistic regime in the three and higher dimensions. Ma and Xu [12,13] by carefully studying the one dimensional Schrödinger equation generalized to the three dimensions radial Schrödinger equation with spherically symmetric potential simplify making the replacement z → r. The proper quantization rule written as…”
Section: Proper Quantization Rule and Formula Methodsmentioning
confidence: 99%